Вып. 4: Тройные окисные системы; Диаграммы состояния силикатных систем - Барзаковский В. П. Валентин Павлович; Лапин В. В. Владимир Васильевич; Бойкова А. И. Александра Ивановна; Курцева Н. Н. Нина Николаевна (1974, 1974)
Авт. указ. на обороте тит. л.